Reduced supply of monocyte-derived macrophages leads to a transition from nodular to diffuse lesions and tissue cell activation in silica-induced pulmonary fibrosis in mice - Shichino, Shigeyuki; Abe, Jun; Ueha, Satoshi; Otsuji, Mikiya; Tsukui, Tatsuya; Kosugi-Kanaya, Mizuha; Shand, Francis H W; Hashimoto, Shin-Ichi; Suzuki, Hiroshi I; Morikawa, Teppei; Inagaki, Yutaka; Matsushima, Kouji (The American journal of pathology, 2015)
Pulmonary fibrosis (PF) is an intractable disorder with a poor prognosis. Lung macrophages have been reported to regulate both progression and remission of bleomycin-induced diffuse PF. However, it remains unclear how macrophages contribute to silica-induced progressive nodular PF and the associated tissue cell responses in vivo. We found that lack of monocyte-derived macrophages results in the formation of diffuse PF after silica instillation. We found that the proportion and the number of monocyte-derived macrophages were persistently higher in silica-induced progressive PF compared with bleomycin-induced PF. Surprisingly, in Ccr2(-/-) mice, in which monocyte-derived macrophage infiltration is impaired, silica administration induced diffuse PF with loose nodule formation and greater activation of tissue cells. In the diffuse lesions, the distribution of epithelial cells, distribution of myofibroblasts, and architecture of the basement membrane were disrupted. Consistent with the development of diffuse lesions, genes that were differentially expressed in CD45(-) tissue cells from the lung of wild-type and Ccr2(-/-) mice were highly enriched in human diffuse, progressive PF. In gene ontology network analyses, many of these genes were associated with tissue remodeling and included genes not previously associated with PF, such as Mmp14, Thbs2, and Fgfr4. Overall, these results indicate that monocyte-derived macrophages prevent transition from nodular to diffuse silica-induced PF, potentially by regulating tissue cell responses.